Respons KH. Saifuddin Zuhri Terhadap Pendudukan Yahudi di Palestina Tahun 1936-1948 - Syahroni, Roni; Rusmana, Dadan; Thohir, Ajid; Salam, Muhajir; Asep Achmad Hidayat (INDO PUBLISHING, 2025)
This study explores the response of KH. Saifuddin Zuhri, one of Indonesia’s prominent Islamic scholars and independence fighters, to the Jewish occupation of Palestine during the period 1936–1948. This period was marked by escalating conflict between the Palestinian population and Zionist groups supported by Britain under the British Mandate for Palestine. The focus of this research is on how KH. Saifuddin Zuhri, as part of the Indonesian Islamic elite, viewed and responded to the Palestinian issue, which at the time had become a central concern in the Islamic world. The study employs a historical method consisting of four main stages: heuristics, source criticism, interpretation, and historiography. The findings reveal that KH. Saifuddin Zuhri consistently opposed the Jewish occupation of Palestine through his writings, speeches, and advocacy in both religious and national forums. His response was rooted in the spirit of Islamic solidarity (ukhuwah Islamiyah) and anti-colonial principles that formed part of the broader struggle of the global Muslim community during that era. These findings indicate that the Palestinian issue was not only a concern for the Arab world but also received serious attention from Indonesian